A Survey of The Physical Fitness Level Of The Men's Basketball Team National Sports Week (PON) Bangka Belitung 2020 - Ridho Pamungkas; Angkit Kinasih; Kristiawan P. A. Nugroho (Journal Physical Education, Health and Recreation, 2020)
Physical fitness is the ability of a person to carry out daily activities easily without excessive fatigue and still has a reserve of energy to do other activities.Through good physical fitness, the aim is to create a future generation excels in all aspects can be realized. The problem formulated is how the level of physical fitness of the PRA PON Bangka Belitung Men's Basketball Team 2020. The aim of this study is to determine the level of physical fitness of the PRA PON Bangka Belitung Men's Basketball Team 2020. The population in this study is Men's Basketball Team 2020 of PRA PON Bangka Belitung with 12 athletes. The sample in this study amounted to 12 athletes. The sampling technique used is total sampling. The method of data collection uses the survey method using the Indonesian Physical Fitness Test (TKJI) method for ages 18-21 years and documentation